Synthesis and Characterization of Some New Sn (II) Aromatic Schiff Base Complex - Srivastava, Shekhar (Asian Journal of Chemistry, 2010)
Thirty two complexes of Sn(II) of the type SnX2·SB (where X = Cl–, Br–; SB = Schiff base) derived from diamines and aromatic carbonyl compounds have been prepared and characterised by elemental analysis, conductivity measurements, IR and XPS data.